Difficult factors in Management of Impacted Dental Prosthesis in Esophagus (Medical Journal of Indonesia, 2005)
A dental prosthesis which ingested and impacted in esophagus, is an emergency case and life threatening, so require immediateesophagoscopy intervention for removing.The objective of this study is to assess some factors can caused dtfficulties in diagnosing and treating the ingested and impacted dental prosthesis in the esophagus and their complications.This retrospective study analyzed patient’s chart whose underwent esophagoscopy for removing the impacted dental prosthesis in Dr. CiptoMangunkusumo General Hospital, Jakarta, Indonesia during a period between January 1997 and December 2003. Neck-chest X-ray and esophagoscopy were performed in all patients to identify the existence of the dental prosthesis as a diagnostic and treatment procedure. The length of time for removing the dental prosthesis was recorded and stated as a less difficult esophagoscopy when it takes time less than 60 minutes and as a difficult esophagoscopy takes 60 minutes or longer. Some risk difficultiesfactors were statistically analyzed.There were 53 patients of ingested dental prosthesis in esophagus. Only 51 cases were analyzed According to the length of time for removingthe dental prosthesis by esophagoscopy, 22 patients were recorded as less difficult cases and 29 patients as difficultcases. Two cases among the cases needed cervicotomy after unsuccessful esophagoscopy removal.The difficultiesto diagnose an impacted dental prosthesis in the esophagus caused by unreliable clinical history, unclear signs and symptoms, unableto be detected by X-ray and was not found during esophagoscopy. The difficulties in treating due to mucosal laceration, edema, bleeding, failure of the first extraction and conformity with the size and shape, the wire outside the dental prosthesis and thelength of time stayed in the esophagus. (Med J Indones 2005; 14: 33-6) Keywords: ingested dental prosthesis, radioluscent foreign body, length of time of esophagoscopy